2005
DOI: 10.1038/sj.jcbfm.9600045
|View full text |Cite
|
Sign up to set email alerts
|

Human Cerebral Blood Flow and Metabolism in Acute Insulin-Induced Hypoglycemia

Abstract: How the human brain functions under conditions of acute hypoglycemia remains a complex question by virtue of the potential simultaneous shifts in processes of perfusion, metabolism, and changing demand. We examined this issue by measuring cerebral blood flow (CBF) and oxidative metabolism (CMRO 2 ) in insulin-induced hypoglycemic (HG) and euglycemic (EG) conditions at rest and during motor activation in normal human subjects using magnetic resonance (MR). Experiments were performed on 12 subjects (9M, 3F). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 29 publications
5
28
0
Order By: Relevance
“…Our data are consistent with this hypothesis and with prior studies using fMRI-BOLD demonstrating that the hypothalamus is responsive to changes in systemic glucose levels (13)(14)(15)(16)(17). On the other hand, previous studies investigating the effects of hypoglycemia on regional CBF in nondiabetic subjects have not identified an increase in hypothalamic blood flow following insulin-induced hypoglycemia (22,24,25). This may be because the hypothalamus is a very small brain region, making it difficult to detect significant changes in blood flow when compared with larger brain regions.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our data are consistent with this hypothesis and with prior studies using fMRI-BOLD demonstrating that the hypothalamus is responsive to changes in systemic glucose levels (13)(14)(15)(16)(17). On the other hand, previous studies investigating the effects of hypoglycemia on regional CBF in nondiabetic subjects have not identified an increase in hypothalamic blood flow following insulin-induced hypoglycemia (22,24,25). This may be because the hypothalamus is a very small brain region, making it difficult to detect significant changes in blood flow when compared with larger brain regions.…”
Section: Discussionsupporting
confidence: 82%
“…PASL is an indirect measure of neuronal activity believed to reflect changes in metabolic state because there is a clear relationship between changes in the local rate of oxygen consumption and changes in local tissue blood flow (20). Although previous studies have investigated the effects of hypoglycemia on CBF in nondiabetic subjects, the current study examined the effects of small glucose decrements within the normal range, whereas earlier studies measured CBF after moderate hypoglycemic levels (plasma glucose Յ60 mg/dl) were achieved (22,24,25). As a result, we were able to investigate the time sequence relationship between hypothalamic activation and the initiation of the counterregulatory hormonal response.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…2 Although the mechanisms of HAAF have not been fully elucidated, a picture is emerging in which a series of cerebral adaptations, including altered fuel transport and/or metabolism, lead to defective glucose counter-regulation and impaired hypoglycemia awareness. 3 The cerebral response to hypoglycemia in the healthy brain involves changes in regional blood flow 4,5 and sequential adjustments in cerebral metabolism in order to provide sufficient fuel for brain activity. As the levels of glucose, the principal cerebral energy substrate, drop from 5 to B3 mmol/L in plasma, cerebral metabolic rate of glucose (CMRglc) and cerebral metabolic rate of oxygen (CMRO 2 ) are preserved [6][7][8] despite lower brain glucose uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Human and animal studies showed that insulin-induced hypoglycemia is associated with increased cerebral blood flow in different brain areas, including the hypothalamus (42,58). Hypoglycemia-induced increases in cerebral blood flow could increase nutrient availability to brain cells during energy deficit.…”
mentioning
confidence: 99%